Female education in Iraq 1921-1958 - A historical Study- - حيدر حميد رشيد زينب هاشم جريان (College of Education for Women, 2019)
In spite of the foundation of Iraqi state in 1921 and the formation of the new features of the modern state, however, the inherited costumes and traditions sustained in the conservative society. But due to the development that inflicted to the Iraqi society and the development of the staff in all fields and requirement conducting to female learning. After WW II and the 1950s, women get out of their houses to seek learning by approaching the doors. What is positive about that phase was the formation of the College of Queen A'liya which is regarded as a positive indicator. In any case the Iraqi family encouraged women to be indulged in higher education. Calling the college Queen A'liya